SISTEM TUMPANGSARI DAN INTEGRASI TERNAK TERHADAP PERUBAHAN SIFAT FISIK DAN KIMIA TANAH DI TANAH LITOSOL - Suroyo Suroyo; Suntoro Suntoro; Suryono Suryono (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2013)
Title : Intercropping and Livestock Integration System : Changes in Physical and Chemical Properties of Litosol. Study sites located in the village Geneng duwur, District Gemolong, Sragen regency, Central Java with litosol soil type. Study sites are located between 7 º 23'10 "latitude and 7 º 23'17" latitude and 110 º 50'28 "E to 110 º 50'24" E with altitude between 150 masl to 155 masl. The experiment was conducted in February 2010 to November 2010. The purpose of the study: (1) Knowing the integrated effect of intercropping with cattle on soil physical properties, (2) Knowing the effect of intercropping systems are integrated with livestock on soil chemical properties. The study design used in this study is complete randomized block design consisting of two factors: factor 1: integration of cattle consisting of 4 standard (I0 = no cattle integration (0 years); I1 = 1 year of integration of cattle ; I2 = integration of cattle 2 years; I3 = integration of cattle 3 years) and factor 2: cropping system consisting of a 3 stage (K = monoculture cropping systems with groundnut crop; J = monoculture cropping systems with corn; KJ = cropping system intercropped with maize crop peanuts). Research results indicate that: (1) intercropping system does not significantly affect the improvement of soil physical properties include: soil density, volume weight of soil, field capacity, porosity; integration of livestock significantly affect the improvement of soil physical properties include: density of the soil, volume weight of soil, field capacity and soil porosity, (2) intercropping system did not significantly affect the chemical properties of soil improvement which include: soil organic matter, total soil N and soil pH; integration of livestock significantly affect the chemical properties of soil improvement material covering soil organic matter, total soil N and soil pH.